Implementasi Kebijakan Penguatan Dimensi Profil Lulusan Melalui Kegiatan Kewirausahaan Di SMP Negeri 18 Gresik: Analisis Berdasarkan Teori Merilee S. Grindle - Sulistiyani, Evi; Purwoko, Budi; Hazin, Mufarrihul (Jurnal Pendidikan : Riset dan Konseptual, 2026)
This research is motivated by the need to strengthen the eight dimensions of the graduate profile at SMP Negeri 18 Gresik through entrepreneurship activities as part of the implementation of the character education policy. This study aims to analyze the implementation of the policy using Merilee S. Grindle's policy implementation model, which emphasizes two main aspects: the context of implementation and the content of the policy. The study used a qualitative approach with data collection techniques in the form of interviews, observations, and documentation studies, and was analyzed descriptively. The results show that the policy implementation has been quite effective, demonstrated by teacher involvement, school support, and student participation in the entrepreneurship program. The activities implemented have been able to develop several important character traits such as creativity, independence, responsibility, and cooperation. However, several obstacles were still encountered, including limited availability of facilities, variations in student motivation, and the need for increased intensive mentoring. Overall, the entrepreneurship program has contributed positively to shaping student profiles that are in line with the demands of the Independent Curriculum and the needs of 21st-century competencies